A biofuels outlook for the U.S. and Brazil and what it might mean for sustainable development goal 7 - Whistance, Jarrett; Debnath, Deepayan; Thompson, Wyatt (Frontiers in Chemical Engineering, 2024)
Sustainable Development goals set out at the United Nations with broad support include targets relating to food security, energy access, and the environment. Some national policies have turned to renewable fuels to achieve energy and environmental goals, with biofuel use mandates applied in countries that account for significant market shares. However, the context in which the development goals were set and these biofuel policies put in place might differ from current and future conditions. The scope for biofuel expansion might be restrained by technical limits on blending rates, slower future growth in transportation energy demand after the pandemic, and the interactions with feedstock and other agricultural commodity markets, which could take different forms given larger biofuel volumes and other changes. Considering the expected policies and broader context, this study provides a 10-year outlook for biofuel use, production, feedstock demands, and other related variables with a primary focus on the United States and Brazil. We find scope for increasing biofuel use in both countries, particularly for biomass-based diesel, in the projection period and growing displacement of petroleum product greenhouse gas emissions, which is consistent with sustainable development goal seven.